1975
DOI: 10.1038/ki.1975.56
|View full text |Cite
|
Sign up to set email alerts
|

Influence of glomerular filtration rate on the rate of para-aminohippurate secretion by the rat kidney: Micropuncture and clearance studies

Abstract: Net secretion rate of para-aminohippurate (PAH) in the proximal convolution of the rat kidney changes concomitantly with single nephron glomerular filtration rate (GFR) and intratubular flow rate. Reabsorption of PAH in the proximal convolution is negligible. The PAH concentration profile along the length of the proximal convolution does not change markedly with variations in GFR. Net PAH secretion by single nephrons, measured at the end of proximal convolutions, is about one-half that measured at the begin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…It is now recognized that one of the mechanisms serving to control the rate of glomerular filtration operates at the single nephron level and responds to changes in some correlate of the flow rate in the early distal nephron (13)(14)(15)(16)(17). In a general sense, the magnitude of a change in SNGFR, in relation to the magnitude of a change in loop of Henle flow rate, is an 1, suppression of SNGFR by native fluid flowing through the loop of Henle was 4.2 nl/min (50%) less in rats fed a high protein diet, compared with rats fed a low protein diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now recognized that one of the mechanisms serving to control the rate of glomerular filtration operates at the single nephron level and responds to changes in some correlate of the flow rate in the early distal nephron (13)(14)(15)(16)(17). In a general sense, the magnitude of a change in SNGFR, in relation to the magnitude of a change in loop of Henle flow rate, is an 1, suppression of SNGFR by native fluid flowing through the loop of Henle was 4.2 nl/min (50%) less in rats fed a high protein diet, compared with rats fed a low protein diet.…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism capable of effecting changes in the determinants of GFR is the individual-nephron negative-feedback control pathway, the tubuloglomerular (TG) feedback system (13)(14)(15)(16)(17). This system serves to adjust glomerular vascular resistance (17)(18)(19) and Kf (17) in response to variations of some correlate of the early distal tubule flow rate, thereby altering the same determinants of filtration that are altered by protein feeding.…”
Section: Introductionmentioning
confidence: 99%
“…The maintained net rate of PAH secretion following NTS is of interest in view of the recent report by Haberle [ 17] that net secretion of PAH in the proximal convoluted tubule in the rat changes concurrently with the single nephron GFR and intratubular flow rate. This is in contrast to the classical concept which implies that each proximal tubule cell pos sesses a limited number of PAH-transporting sites and the net rate of secretion occurs when all the sites are occupied.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that PAH concentration profile along the length of the proximal convolution does not change markedly with variations in GFR. 23 The fraction of PAH that passes the glomerulus and enters tubular cells of the nephron (via peritubular capillaries) is completely secreted. 9 Consequences of renal dysfunction for pharmacotherapy in SCI For proper pharmacotherapy after SCI, early renal dysfunction detection is critical.…”
Section: Reduced Glomerular Filtration Ratementioning
confidence: 99%